Plant-Based Fat, Dietary Patterns Rich in Vegetable Fat and Gut Microbiota Modulation - Muralidharan, Jananee; Galiè, Serena; Hernández-Alonso, Pablo; Bulló, Monica; Salas-Salvadó, Jordi (Frontiers in Nutrition, 2019)
Diet is advocated as a key factor influencing gut microbiota. Several studies have focused on the effect of different carbohydrates, mainly fiber, on gut microbiota. However, what remains to be elucidated is the impact of a key component of diet that is widely debated upon: dietary fats. This review highlights the importance to understand the source, quality and type of fats that could differentially modify the intestinal microbiome. Fats from plant-based sources such as nuts, or vegetable oils have shown positive alterations in gut microbiota biodiversity both in in vivo and in vitro studies. Nuts and other plant-based fat sources, dietary patterns (e.g. Mediterranean diet) rich in polyunsaturated and monounsaturated fats and, in some cases, polyphenols and other phytochemicals, have been associated with increased bacterial diversity, as well beneficial butyrate-producing bacteria imparting a positive metabolic influence. It is with this interest, this narrative review brings together evidences on different plant-based fat sources, dietary patterns rich in vegetable fats and associated changes in gut microbiota.